Inclusive Tourism for Children with Autism Spectrum Disorder: Parental Perceptions in Bandung City - Taufik Ramadhan Zain, Mochammad; Sadhana, Brian; Shihabi , Al Mukti Rosyid; Nugraheni, Wahyu Nur; Utami , Nadya Rechtta (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
This study aims to identify the perceptions of parents who have children with autism spectrum disorder (ASD) regarding the safety and comfort needed by children when participating in tourist activities. This study uses a descriptive qualitative approach. Data was collected through in-depth interviews with parents of children with ASD. Most children with ASD face unique challenges and difficulties in life, particularly when participating in tourism activities. The study findings indicate that tourism activities are significantly influenced by safety and comfort factors. Perceptions of safety include parents’ concerns and anxieties. Perceptions of comfort involve the availability of an environment that addresses the child’s sensory, emotional, and social needs. Therefore, this study highlights the importance of implementing inclusive tourism for children with ASD, tailored to their needs and preferences regarding the unique challenges and issues they face, to create a enjoyable travel experience.